2023
DOI: 10.1002/ecs2.4417
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patterns in ecosystem phenology near Palmer Station, Antarctica, from the perspective of the Adélie penguin

Abstract: Climate change is leading to phenological shifts across a wide range of species globally. Polar oceans are hotspots of rapid climate change where sea ice dynamics structure ecosystems and organismal life cycles are attuned to ice seasonality. To anticipate climate change impacts on populations and ecosystem services, it is critical to understand ecosystem phenology to determine species activity patterns, optimal environmental windows for processes like reproduction, and the ramifications of ecological mismatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…At Béchervaise Island where the fast ice is more extensive, penguin reproductive success is reduced (Emmerson & Southwell, 2008 ) while areas with less sea ice during the breeding season have higher foraging performance and breeding success (Watanabe et al., 2020 ). Phenology is also influenced by extensive fast ice delaying nest arrival and clutch initiation (Cimino et al., 2023 ; Emmerson et al., 2011 ), as well as other environmental variables like early snowmelt correlating to an earlier clutch initiation (Lynch et al., 2009 , 2012 ). Near Palmer Station there is a negative relationship between late clutch initiation and breeding success, where sea ice and effects from precipitation and island geomorphology delayed clutch initiation (Cimino et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…At Béchervaise Island where the fast ice is more extensive, penguin reproductive success is reduced (Emmerson & Southwell, 2008 ) while areas with less sea ice during the breeding season have higher foraging performance and breeding success (Watanabe et al., 2020 ). Phenology is also influenced by extensive fast ice delaying nest arrival and clutch initiation (Cimino et al., 2023 ; Emmerson et al., 2011 ), as well as other environmental variables like early snowmelt correlating to an earlier clutch initiation (Lynch et al., 2009 , 2012 ). Near Palmer Station there is a negative relationship between late clutch initiation and breeding success, where sea ice and effects from precipitation and island geomorphology delayed clutch initiation (Cimino et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a R² of 0.70, our low-resolution TDR-based model provides comparable results to other DLW calibrations based on high-resolution accelerometers on marine and terrestrial species like Adélie penguin (R² = 0.75) (Hicks et al, 2020) or little penguins (R² = 0.78) (Sutton et al, 2021) or polar bear (R² = 0.70) (Pagano and Williams, 2019). This equation could be applied to the numerous Adélie penguin long-term TDR data collected across Antarctica (Cimino et al, 2023; Lescroël et al, 2023; Riaz et al, 2020), therefore offering a great opportunity to reliably investigate regional variations in energy budgets. In line with what was previously known (Hicks et al, 2020), we showed that assigning different calibration coefficients to different behaviour enhanced predictive power of our model.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors accepted to affect krill populations that could have cascading effects in chinstrap penguin abundance are the changes on sea ice cover caused by climate change 4 , 5 , 14 , the increased competition for krill caused by the recovery of whale populations and the growth of krill-trawling fisheries 15 18 . A recent publication 19 also showed that the joint effects of sea ice, storms and cloudy conditions affect the phenology of low and mid trophic levels of marine ecosystems in the Antarctic Peninsula, therefore having a bottom-up effect over top-predators, particularly, causing a mismatch between the peak food availability and penguins’ breeding.…”
Section: Introductionmentioning
confidence: 99%